Making decision with an alternative mind-set: Predicting entrepreneurial intention toward f-commerce in a cross-country context. (May 2021) - Ashraf, Mohammad Ali; Alam, Mirza Mohammad Didarul; Alexa, Lidia
Abstract: Facebook commerce ( f -commerce) is a relatively new online entrepreneurial initiative that employs Facebook as an electronic space to promote and implement commercial trades. Available empirical research on f -commerce indicates that research on factors affecting entrepreneurial intention toward f -commerce is sparse. Grounded on the theory of bounded rationality, this paper investigates the drivers of f -commerce entrepreneurial intention of young generation on a cross-nationality basis. Data were gathered from the young pool of senior university students from three countries through self-administered questionnaire. The data were analyzed utilizing PLS-SEM. Findings indicate that all of the predictors appear to be robust in predicting f -commerce entrepreneurial intention of the young adults of all three countries. These outcomes will help potential young entrepreneurs in selecting f -commerce entrepreneurship as an option for their future career. Highlights: The predictors of entrepreneurial intention toward f -commerce are explored. The study deploys the Theory of Bounded Rational Planned Behavior (TBRPB). Responses of the university students are focused and taken from Romania, Malaysia, and Bangladesh. PLS-SEM and Multi-Group Analysis (MGA) are employed. High model predictability is ensured in all the country contexts.